Identifying resistance to root-knot nematodes in Capsicum genotypes (Bioscience Journal, 2018)
The present study aimed to evaluate Capsicum accessions for resistance to Meloidogyne incognita race 3, Meloidogyne javanica and Meloidogyne enterolobii. Two experiments with different genotypes of hot and sweet peppers were carried out in a completely randomized design. The first experiment was conducted in a 31 x 3 factorial scheme with 27 genotypes of Capsicum annuum, two cultivars of hot pepper, one line of Capsicum frutescens and tomato 'Santa Cruz Kada', and three species of nematodes (M. incognita race 3, M. javanica and M. enterolobii). In the second experiment, we used a factorial scheme 39 x 3 with 36 accessions of C. annuum, two hot pepper cultivars and the 'Santa Cruz Kada' tomato and three nematodes species mentioned earlier. The total number of eggs and second-stage juveniles (TNEJ), number of eggs and second-stage juveniles per gram of root (NEJGR), reproduction index (RI) and reproduction factor (RF) were evaluated. Based on RI and RF, the genotypes CNPH 185, CNPH 187 and CNPH 680 were resistant and very resistant to M. incognita race 3 and M. javanica, simultaneously. The C. frutescens line presented resistance to the three root-knot nematode species.